The economic indicators impact on economic growth a case of Southeast Asian countries / Azmin Jamaludin - Jamaludin, Azmin (Perpustakaan Tun Abdul Razak UiTM Caw Sabah, 2012)
This paper aims to determine the causality relationship between Foreign Direct Investment, Exports and Imports and Growth and to examine the relationship between the dependent variable and independent variables for South East Asia countries over a period of time from 1981 to 2010. For this purpose, Johansen Cointegration and Granger-causality test will be used to determine the causal relationship between FDI, export and import and growth in the long run. The empirical result for causality relationship found that Malaysia is independence where there is no long run causality relationship between variables. Finding for Indonesia, it was found that there is unidirectional long run causality relationship between GDP and import where the direction is from GDP Granger cause import. For Singapore and Thailand, the results found that there is causality relationship between variables in the long run where for Singapore it was found the existence of GDP-led FDI , Export-led FDI, Import-led FDI and there also bidirectional causality between import and export. Finding of GDP-led FDI and Export-led FDI were also found in Hsiao and Hsiao (2006) paper, this indicates that the finding is valid. Other than that Hsiao and Hsiao (2006) also found that there is no significant causality relationship in the long run between variables for Malaysia country. Meanwhile, there is existence of export-led FDI and Export-led Import for Thailand countries. In conclusion, the foreign trade gives an impact towards the economic growth in the long run. Therefore to stabilize the economic growth, role of FDI is important in transferring technology and knowledge increases. The role of import and export also important in stimulating the economic growth for Southeast Asian countries.